Asymmetric oceanic response to a hurricane: Deep water observations during Hurricane Isaac. Issue 10 (19th October 2016) - Spencer, Laura J.; DiMarco, Steven F.; Wang, Zhankun; Kuehl, Joseph J.; Brooks, David A.
Abstract: The eye of Hurricane Isaac passed through the center of an array of six deep water water‐column current meter moorings deployed in the northern Gulf of Mexico. The trajectory of the hurricane provided for a unique opportunity to quantify differences in the full water‐column oceanic response to a hurricane to the left and right of the hurricane trajectory. Prior to the storm passage, relative vorticity on the right side of the hurricane was strongly negative, while on the left, relative vorticity was positive. This resulted in an asymmetry in the near‐inertial frequencies oceanic response at depth and horizontally. A shift in the response to a slightly larger inertial frequencies ∼1.11 f was observed and verified by theory. Additionally, the storm passage coincided with an asymmetric change in relative vorticity in the upper 1000 m, which persisted for ∼15 inertial periods. Vertical propagation of inertial energy was estimated at 29 m/d, while horizontal propagation at this frequency was approximately 5.7 km/d. Wavelet analysis showed two distinct subinertial responses, one with a period of 2–5 days and another with a period of 5–12 days. Analysis of the subinertial bands reveals that the spatial and temporal scales are shorter and less persistent than the near‐inertial variance. As the array is geographically located near the site of the Deep Water Horizon oil spill, the spatial and temporal scales of response have significant implications for the fate, transport, and distribution of hydrocarbons following a deep water spill event. Key Points: The oceanic response to hurricane forcing is asymmetric with respect to the storm's trajectory Oceanic response was limited to about 15 inertial periods